2014
DOI: 10.3390/ijerph111010292
|View full text |Cite
|
Sign up to set email alerts
|

Ecohealth Approach to Urban Waste Management: Exposure to Environmental Pollutants and Health Risks in Yamoussoukro, Côte d’Ivoire

Abstract: Poor waste management is a key driver of ill-health in urban settlements of developing countries. The current study aimed at assessing environmental and human health risks related to urban waste management in Yamoussoukro, the political capital of Côte d'Ivoire. We undertook trans-disciplinary research within an Ecohealth approach, comprised OPEN ACCESS Int. J. Environ. Res. Public Health 2014, 1110293 of a participatory workshop with stakeholders and mapping of exposure patterns. A total of 492 randomly selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
3
11
0
1
Order By: Relevance
“…Furthermore, communication between levels of government appeared to be inconsistent and the viewpoints of government representatives on waste management practices and recommendations for creating regulations differed greatly between government departments. This lack of coherence supports the need for a more integrated view of human and environmental health within the government [41,43]. Both farmers and policymakers also perceived that there was a lack of connection between human, animal, and environmental health, demonstrating that neither group viewed health in a holistic matter.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Furthermore, communication between levels of government appeared to be inconsistent and the viewpoints of government representatives on waste management practices and recommendations for creating regulations differed greatly between government departments. This lack of coherence supports the need for a more integrated view of human and environmental health within the government [41,43]. Both farmers and policymakers also perceived that there was a lack of connection between human, animal, and environmental health, demonstrating that neither group viewed health in a holistic matter.…”
Section: Discussionmentioning
confidence: 86%
“…Future research could evaluate regulations to identify how they can be better integrated and implemented to improve both human and environmental health. Combining health and environmental risk assessments can enable a deeper understanding of environmental hazards and disease burdens linked to poor waste management [43].…”
Section: Discussionmentioning
confidence: 99%
“…L'analyse spatiale apporte un nouvel éclairage sur l'exposition potentielle aux dangers environnementaux en milieu urbain. Vivre près d'une eau stagnante ou d'un tas d'ordures suppose a priori un risque de maladies plus élevé comme conséquence de l'exposition aux dangers environnementaux (Kouamé et al, 2014). Le fait d'avoir plus de mères éduquées, une proportion relativement faible d'enfants malnutris, l' accès à l'eau potable et à l'assainissement, ainsi que la nature du sol dans les quartiers lotis expliqueraient une occurrence faible des maladies en zones loties (El-Fadel et al, 2014).…”
Section: Graphique 2 : Projection Des Groupes Sur Le Plan Factoriel Dunclassified
“…In Côte d'Ivoire the nutrient loading of nitrogen to aquifers from on-site sanitation systems is largely unknown (Nyenje et al, 2013). For instance, in the city of Yamoussoukro, it was recently reported that the level of nitrogen has increased in the lake waters due to anthropogenic activities (Kouamé et al, 2014). Generally, the solid waste sector is poorly managed and wastes are open dumped without any treatment or reuse options.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the solid waste sector is poorly managed and wastes are open dumped without any treatment or reuse options. Furthermore, untreated effluents from septic tanks are discharged to the environment including the lakes without any control (Kouamé et al, 2014). Lack of sanitation in Yamoussoukro has considerably affected the environment and human health (Arvidsson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%